The Effect of Problem Based Learning Model on Students' Analytical Thinking Ability Based on Learning Outcomes of Islamic Cultural History Subject (SKI) - Siti Seituni; Muhammad Rizal; Anis Febriyanti (Intiqad: Jurnal Agama dan Pendidikan Islam, 2023)
This article describes the influence of the problem-based learning model on students' analytical thinking skills based on the learning outcomes of Islamic Cultural History (SKI) subjects. The modern concept of learning requires students to be creative, responsive and active in searching, selecting and finding, analysing, concluding and reporting learning outcomes. In this study the researcher aimed to find out whether there was an influence between the independent X-variable on the Y-variable. There was a significant effect between problem-based learning on analytical thinking of eighth grade students of MTs Sarji Ar-Rasyid. The results of the analysis obtained t count 0.501 with a significant value of 0.013 which is less than a significance level of 0.05 while the value of R square = 25.1%. The magnitude of the effect of problem-based learning on the analytical thinking of eighth grade students at MTs Sarji Ar-Rasyid is 25.1%, this is shows that 74.9% of the analytical thinking of students is influenced by other factors (internal factors or external factors) that require advanced research.